Tax collection: a way of loan. An approach to the main financial groups in the Castile of Catholics Monarchs - Ortega Cera, Ágatha (En la España Medieval, 2020)
. The main purpose of this paper is to define as a group the so-called elite of tax collection, focusing on the individuals that could be grouped under this denomination or the common characteristics that the great financiers who worked in the service of Catholic Monarchs had. The contractual relationship between the Crown and these power groups through the tax collection system, which can be understood as a loan system, will also be addressed in this article